Soft-tissue modification in Class III non-growing patients treated with clear aligners: a prospective clinical trial - R. Lione; C. Pavoni; F. Gazzani; F. C. De Razza; F. C. De Razza; L. Lugli; P. Cozza (Frontiers in Dental Medicine)
IntroductionThe aim of the present prospective study was to assess the soft tissue modifications induced by camouflage treatment with clear aligners in adult patients with mild Class III malocclusion.MethodsPatients were consecutively enrolled in the study sample according to the following inclusion criteria: adult age (≥19 years), permanent dentition including second permanent molars, skeletal Class I or slight Class III (−2° < difference between sella-nasion^ point A and sella-nasion^ point B < +2°), normal skeletal divergence pattern (SN^GoGn, 27°-37°), Class III canine and molar relationship at baseline (T0) with moderate lower arch crowding (≤+4 mm), and good compliance with aligners and elastics (≥20 h/day). All the participants underwent the lower distalization protocol, which included extraction of the lower third molars before starting treatment and a 50% sequential lower distalization, and Class III intermaxillary elastics (1/4 in., 6.5 oz) from buttons on the upper first molars to precision cuts at the level of the lower canines to reinforce the anchorage. Lateral cephalograms were taken at T0 (before treatment) and at the end of the clear aligner treatment (T1) with an average time interval of 24 ± 6 months. A customized digitization regimen and cephalometric analysis were created to assess the esthetic outcomes at T1. The significance level was set at P < 0.05.ResultsThe lower distalization supported by Class III elastics resulted in a slight improvement of the facial esthetic profile with no significant changes in the lower third of the face. A mildly better projection of the upper lip was detected at the end of treatment, mainly due to the extensive use of Class III elastics.DiscussionThe lower distalization supported by Class III elastics determined slight improvement of the facial aesthetic profile with no significant changes in the lower third of the face. A mild better projection of the upper lip was detected at the end of treatment, mainly due to the extensive use of Class III elastics.